The effect of surface lithology on arsenic and other heavy metals in surface water and groundwater in Mustang Valley, Nepal Himalaya - Emerman, Steven H.; Nelson, Janae R.; Carlson, J. Kade; Anderson, Tracy K.; Sharma, Anusha; Adhikari, Basanta R. (Journal of Nepal Geological Society, 2014)
Recent studies have shown that elevated groundwater as occurs even in Kathmandu and Pokhara Valleys in Nepal, two tectonic valleys well upstream of the floodplain of the Ganges River. Moreover, studies in both valleys showed surface water As to be statistically indistinguishable from groundwater As, which led to the fluvial recharge model in which elevated groundwater As results from losing streams with elevated As, which is a consequence of rapid erosion caused by a combination of monsoon climate, tectonic uplift and deforestation. The objective of this study was to further test the fluvial recharge model in Mustang Valley, the third major tectonic valley in Nepal Himalaya far upstream from the floodplain of the Ganges River. In May 2011 water samples were collected from 33 surface water sites (24 directly from streams and 9 from canals, pipes or taps fed by streams) and 24 groundwater sites (10 directly from springs and 14 from pipes or taps fed by springs). The WHO As Standard was exceeded in 47% of surface water samples and 79% of groundwater samples, including all nine functioning water taps in Lo-Manthang, the largest village. Separating samples into a high- As Region I (geometric mean As = 0.071 mg/L) and a low-As Region II (undetectable As for 85% of samples) showed that surface water As and groundwater As were statistically indistinguishable within each region. Only Region I receives overland flow from the exposed Mustang and Mugu Granites. The correspondence between groundwater As and watershed surface lithology is further evidence for the fluvial recharge model.